Sistemas catalíticos ródio-arilfosfinas bidentadas com seletividade Markovnikov para a hidroformilação de alilbenzenos de ocorrência natural - Gabriel Matos Vieira (2016)
The industrial synthesis of the fragrance components canthoxal and helional is performed in four steps starting, respectively, from estragole and safrole, which are naturally occurring allyl-benzenes. The hydroformylation (1,2 formal addition of a hydrogen and a formyl group into a C-C double-bond, resulting in a homologous aldehyde) is an alternative one-step route for the synthesis of these fragrances. It allows their obtainment via an economic and sustainable way. The synthetic challenge is to control the regioselectivity of this reaction, which should lead to the introduction of the formyl group in position 2 of the allylic chain.The catalyst system was generated in situ by combining [Rh(cod)(OMe)]2 pre-catalyst and bidentated arylphosphines. The reaction parameters varied were: concentration of the phosphorus ligand and the catalyst precursor, temperature (40 to 100 °C), partial pressures of hydrogen and carbon monoxide (10-20 bar), and solvent. The critical parameters for controlling the regioselectivity were the type of auxiliary ligand, the molar ratio P/Rh and the solvent. With Xantphos as ancillary, it was possible to obtain 97% selectivity to the linear aldehyde. The selectivity to the branched aldehyde is known to be more difficult to achieve. In toluene, it was demonstrated that with the use of chelating ligands with biting angle near 90o (DPPE, DPPP, and cis-1,2-bis(diphenylphosphino)ethylene), selectivities up to 66% to the branched aldehyde can be reached. Another remarkable aspect is that the selectivity depends markedly on the P/Rhatomic ratio: for DPPP, up to a value of 12, the system displays a preference for linear aldehyde (near 70%); from a value of 13 to 60 there is a decrease in activity and the regioselectivity is reversal, favoring the branched aldehyde (c.a. 60%). Under the same conditions, in ethanol ormethanol the system is inactive, in hexane double bond isomerization is significant, in THF selectivity to the linear product is 60%. Only in aromatic solvent (benzene, toluene, p-cymene) or 1,2-dichloroethane selectivity to branched product is about 60%. Although it seems a modest value, this figure is among the highest ever reported for the hydroformylation for substrates of the kind CH2=CHCH2R. The peculiar selectivity of the catalytic system of rhodium/chelating diphosphines with bite angle near 90o seems to be derived of rhodium species of the type [RhH(PP)2], in which a -donor trans to the hydride is the determinant factor of the selectivity.